The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/mnras/stu2435
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of Type IIn/Ia–CSM supernovae: optical and near-infrared spectra of SN 2012ca and SN 2013dn

Abstract: A growing subset of Type Ia supernovae (SNe Ia) show evidence for unexpected interaction with a dense circumstellar medium (SNe Ia-CSM). The precise nature of the progenitor, however, remains debated owing to spectral ambiguities arising from a strong contribution from the CSM interaction. Late-time spectra offer potential insight if the post-shock cold, dense shell becomes sufficiently thin and/or the ejecta begin to cross the reverse shock. To date, few high-quality spectra of this kind exist. Here we report… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 83 publications
(95 reference statements)
1
65
0
Order By: Relevance
“…Silverman et al (2013) reported on the discovery of additional SNe Ia-CSM in archival and Palomar Transient Factory (PTF; Law et al 2009) data, raising the total number to 16 objects. Two more events have been reported since this study (Inserra et al 2014;Fox et al 2015). Curiously, Anderson et al (2012) have shown that the distribution of SN IIn locations with respect to star formation lies between those of SNe Ia and those of SNe from more massive stars.…”
Section: Introductionmentioning
confidence: 57%
“…Silverman et al (2013) reported on the discovery of additional SNe Ia-CSM in archival and Palomar Transient Factory (PTF; Law et al 2009) data, raising the total number to 16 objects. Two more events have been reported since this study (Inserra et al 2014;Fox et al 2015). Curiously, Anderson et al (2012) have shown that the distribution of SN IIn locations with respect to star formation lies between those of SNe Ia and those of SNe from more massive stars.…”
Section: Introductionmentioning
confidence: 57%
“…Such an envelope might be created by pre-explosion mass loss or a binary interaction. There is mounting evidence for the existence of such dense stellar environments around other transients such as SN Type IIn (Fransson et al 2014, and references therein), SN Type IIb (Nakar & Piro 2014), SN Type Ibn (e.g., Matheson et al 2000;Pastorello et al 2008;Gorbikov et al 2014), and SN Type Ia-CSM (Silverman et al 2013;Fox et al 2015).…”
Section: Shock Breakout or Central Engine?mentioning
confidence: 99%
“…Alternatively, the emitting dust could be interstellar in nature and illuminated by the optical flash (i.e., an "IR echo"). We first test the IR echo scenario by using Equation (2) to estimate the predicted temperature of dust at a distance ofc t 2, which is where the hottest dust is located if heated by the optical/UV flash (e.g., Fox et al 2011Fox et al , 2015. At t≈460 days and given an optical/UV outburst luminosity of L≈3×10 6 L e , the predicted dust temperature is 43 K, significantly less than the temperature estimated at day 460 (T d ≈850±73 K).…”
Section: Post-outburst Re-brightening: Evidence Of Progenitor Survivamentioning
confidence: 99%